Tindak Kejahatan Phising Di Sektor Pelayan Di Universitas Bina Insan Lubuklinggau - Caniago, Koko; Sutabri, Tata (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The rapid advancement of today's technology is very helpful for someone in doing work, one of the technologies that is very developed today is the internet, with the internet, it is very easy for someone to communicate with other people, access data stored on the internet and make it very easy for someone to do their job. but behind the convenience when accessing the internet there are crimes that can attack internet users themselves, one of the crimes is phishing, where phishing is very detrimental to the victim. Phishing is a threat that uses social engineering techniques to trick users by impersonating an authorized entity. Phishing attacks various industrial sectors including the corporate industry, banking, education and others. Factors that cause phishing in online banking services are the lack of user knowledge, psychology, and privacy of social networking services. Therefore, prevention of phishing attacks can be done through computer network security. The research method used in this study is a qualitative method with descriptive techniques.